2021
DOI: 10.1002/eap.2295
|View full text |Cite
|
Sign up to set email alerts
|

Linking land use patterns and pest outbreaks in Bt maize

Abstract: Western corn rootworm, Diabrotica virgifera virgifera LeConte (Coleoptera: Chrysomelidae), is a major pest of maize in the United States and is an invasive pest in Europe. Maize is the only agricultural crop on which western corn rootworm larvae can survive and this insect requires two consecutive years of maize cultivation to complete its life cycle. Transgenic maize producing insecticidal proteins derived from the bacterium Bacillus thuringiensis (Bt) is often used to manage rootworm populations. The first B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 61 publications
1
11
0
Order By: Relevance
“…St. Clair and Gassmann [76] analyzed landscape-level patterns of maize cultivation in past problem fields and in areas surrounding past problem fields in Iowa during the timeframe when these fields failures occurred. These patterns were compared with randomly selected agricultural fields in Iowa during the same time period [76].…”
Section: Resistance To Bt Maize In the Agricultural Landscapementioning
confidence: 99%
See 4 more Smart Citations
“…St. Clair and Gassmann [76] analyzed landscape-level patterns of maize cultivation in past problem fields and in areas surrounding past problem fields in Iowa during the timeframe when these fields failures occurred. These patterns were compared with randomly selected agricultural fields in Iowa during the same time period [76].…”
Section: Resistance To Bt Maize In the Agricultural Landscapementioning
confidence: 99%
“…Clair and Gassmann [76] analyzed landscape-level patterns of maize cultivation in past problem fields and in areas surrounding past problem fields in Iowa during the timeframe when these fields failures occurred. These patterns were compared with randomly selected agricultural fields in Iowa during the same time period [76]. This study found that, not only were past problem fields characterized by higher levels of continuous maize cultivation compared to randomly selected fields, but also that the local landscape around these past problem fields had more continuous maize than randomly selected points [76].…”
Section: Resistance To Bt Maize In the Agricultural Landscapementioning
confidence: 99%
See 3 more Smart Citations